SIFAT FISIK DAN MEKANIK KOMPOSIT SEMEN-CaCl2-AREN DENGAN VARIASI UKURAN SERAT AREN - . Mujtahid; Dody Ariawan; Wijang WR (Prosiding SNST Fakultas Teknik, 2010)
The aim of this research is to investigate bending strength values of arenga-cement composite that based on variation of the fibre particle size. The composite consists of randomized arenga fiber as filler/reinforced and portland cement (50% weight ratio)-CaCl2 (10% weight ratio) mixing as matrix. The bending strength was characterized by Universal Testing Machine and the bending specimens based on ASTM D3039. The bending strength has been measured as a function of the fibre particle size variation (20 mesh, 40 mesh, 60 mesh and 80 mesh). The experiment result indicate that bending strength increase with the decrease of fibre size. The highest bending strength (122,65 MPa) and density (1,52 gr/mm3) were reached at 80 mesh and the lowest water absorption was reached at 88 Kg/cm2 pressing pressure. Based on Scanning Electron Microscope observation, composite with fibre 80 mesh shows a good bond between matrik and fibre. Keywords : arenga-cement composite, fibre particle size and bending strength.